Tinjauan Hukum Ekonomi Syariah terhadap Akad Qardh Studi Kasus GoPay Later - Khaira, Haba Qiestha; Irawan, Anggi (Jihbiz : Jurnal Ekonomi, Keuangan dan Perbankan Syariah, 2024)
Innovation in the financial sector has presented new financing models that integrate technology, including flexible and pay later financing services such as those offered by financial technology (fintech) companies such as GoPay Later. This research aims to conduct a sharia economic law review of the Qardh contract used in the GoPay Later service. The research method used is library research with a descriptive-analytical approach. Data were analysed using a sharia economic perspective and Islamic legal principles related to Qardh contracts. The findings of this research highlight several aspects that need to be considered from a sharia economic law perspective, such as the existence of hidden costs or risks for the parties involved in the transaction. Although the GoPay Later service offers several benefits to its customers, a deeper understanding of sharia economic principles in the context of fintech services is required to ensure compliance with the principles of Islamic law. It is hoped that this research can contribute to the development of regulations and business practices that are more in line with sharia economic principles.